Critique beyond relation: The stakes of working with the negative, the void and the abyss - Chandler, David; Pugh, Jonathan (Transactions - Institute of British Geographers (1965), 2025)
The ‘relational turn’ has been widely embraced in Human Geography and related fields over the last couple of decades as an alternative to the hubris of modern and colonial reasoning. Yet, increasingly, concerns over the extent that contemporary conceptualisations are overly ‘generative’, ‘productivist’ and ‘affirmational’ has come to the fore. There is significant interest in the possibilities for more negative understandings, highlighting failure, attrition, voiding, exhaustion, impotentiality, incompleteness and attributes of ‘non‐relation’. We draw out how, to date, most of these approaches have developed a hermeneutic approach, seeking to bring the negative and the non‐relational into the world as forces of disruption and refusal, holding open other possibilities of knowing and being in the world and enabling alternative political imaginaries. This paper seeks to outline an alternative mode of critique, one that places both relational and negative approaches under the scrutiny of an ‘abyssal’ approach. Here, after Fanon, the world violently forged into the global colour line is bifurcated via the construction of the modern subject, capable of reading itself as a subject in the world and through Human Geography as a field of study. In this always already antiblack world, the goal of ‘Abyssal Geography’ is not to continue worlding the modern subject in new ways, but to analyse and critique the mechanisms and shifts in critical thought through which Human Geography continues to salvage and to redeem the purchase of the modern subject and the world. Short This paper seeks to outline an alternative mode of critique, one that places both relational and negative approaches under the scrutiny of an ‘abyssal’ approach. Here, after Fanon, the world violently forged into the global colour line is bifurcated via the construction of the modern subject, capable of reading itself as a subject in the world and through Human Geography as a field of study.